ECONOMIC CHALLENGES AND CONSUMER PURCHASING BEHAVIOUR: AN INSIGHT FROM ILORIN METROPOLIS IN KWARA STATE, NIGERIA - Mulikat, Abdulraheem (Ekonomski pogledi, 2025)
The Nigerian economy is witnessing significant economic challenges that may affect businesses, individuals and households. These challenges include, exchange rate, interest rate, economic instability and inflation which may have consequent effect on consumer purchasing behaviour. The objective of the research work is to assess the effect of these economic challenges on consumer purchasing behaviour: An insight from Ilorin metropolis in Kwara state Nigeria. Descriptive survey design was adopted for the study and the population comprised of individuals from Ilorin Metropolis. However, the Cochran formula was use to arrive at a sample size of 385 respondents out of which 367 respondents filled and returned the questionnaire.  A structured questionnaire was designed on a five-point likert scale to indicate the degree of respondent’s agreement. One hypothesis was tested using multiple regression analysis. Statistical analyses such as ANOVA, regression, and correlation coefficient were conducted, revealing significant evidence of the influence of economic challenges on consumer purchasing behaviour. The null hypothesis stating that economic challenges have no significant effect on consumer purchasing behaviour was rejected which implies that economic challenges have effect on consumer purchasing behaviour. The study concluded that economic challenges significantly affect consumer purchasing behaviour which has led to a change in consumption pattern, spending habit and purchasing decision. It was recommended that individuals in Ilorin metropolis should develop strategies to cope with the present economic situation and businesses should offer value for money goods and services to meet up with the changing consumer needs. The findings provide empirical evidence of the effect of economic challenges on consumer purchasing behaviour, filling a knowledge gap in the existing literature.
Keywords: economic challenges; consumer purchasing behaviour; inflation; consumer spending; economic instability